The Influence of Board of Directors Busynesss on The Accounting Information Value of Consumer Goods Companies in Indonesia - Gracia Suitella, Maria; Riadi, M Nala; Wijaya, Richy; Muchtar, Susy (CV. Era Digital Nusantara, 2025)
This study aims to analyze the influence of board of directors’ busyness on the value of accounting information in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange. In recent years, the complexity of corporate governance has raised concerns about the effectiveness of oversight, particularly when directors hold multiple directorships. Although many studies have examined the relationship between board busyness and firm performance, research on its impact on accounting information value in emerging markets remains limited. This study addresses that gap by using a sample of 29 consumer goods companies from 2020 to 2024, selected through purposive sampling. The analysis method applied is panel data regression with a fixed effect model. The value of accounting information is proxied by stock price as a market indicator. The results indicate that busy board members significantly and positively influence the value of accounting information, alongside firm size and return on assets (ROA). Meanwhile, leverage shows a significant negative effect. These findings provide empirical contributions to the literature on corporate governance in emerging markets and offer practical insights for managers and investors to strengthen oversight effectiveness and financial information quality.